Use of Waste Generated during the Manufacture of Bioplastics from Sewage Sludge - N. Anes García; F. Blanco Álvarez; A. L. Marqués Sierra (Proceedings, 2021)
There is an evolution and progress that has been taking place in recent years in science and technology and in the evolution of polymers that have created new plastic materials with excellent physical properties and durability. However, the plastic products that are made, generally have several applications, but for a single use, especially if it is in the part of food packaging, or for the pharmaceutical industry, in medical applications. Since these materials are not biodegradable, they remain on the surface of the earth for hundreds of years without considerable changes in their structure, causing pollution and damage to wildlife and the environment. With this research we intend to eliminate these plastics from petroleum derivatives, by biodegradable plastics. At the same time, the use of the generated by-products is sought, giving them an energy, thermal or fertilizer value.